Taurine supplementation for prevention of stroke-like episodes in MELAS: a multicentre, open-label, 52-week phase III trial. Issue 5 (17th April 2018) - Ohsawa, Yutaka; Hagiwara, Hiroki; Nishimatsu, Shin-ichiro; Hirakawa, Akihiro; Kamimura, Naomi; Ohtsubo, Hideaki; Fukai, Yuta; Murakami, Tatsufumi; Koga, Yasutoshi; Goto, Yu-ichi; Ohta, Shigeo; Sunada, Yoshihide
Abstract : Objective: The aim of this study was to evaluate the efficacy and safety of high-dose taurine supplementation for prevention of stroke-like episodes of MELAS (mitochondrial myopathy, encephalopathy, lactic acidosis and stroke-like episodes), a rare genetic disorder caused by point mutations in the mitochondrial DNA that lead to a taurine modification defect at the first anticodon nucleotide of mitochondrial tRNA Leu(UUR), resulting in failure to decode codons accurately. Methods: After the nationwide survey of MELAS, we conducted a multicentre, open-label, phase III trial in which 10 patients with recurrent stroke-like episodes received high-dose taurine (9 g or 12 g per day) for 52 weeks. The primary endpoint was the complete prevention of stroke-like episodes during the evaluation period. The taurine modification rate of mitochondrial tRNA Leu(UUR) was measured before and after the trial. Results: The proportion of patients who reached the primary endpoint (100% responder rate) was 60% (95% CI 26.2% to 87.8%). The 50% responder rate, that is, the number of patients achieving a 50% or greater reduction in frequency of stroke-like episodes, was 80% (95% CI 44.4% to 97.5%). Taurine reduced the annual relapse rate of stroke-like episodes from 2.22 to 0.72 (P=0.001). Five patients showed a significant increase in the taurine modification of mitochondrial tRNA Leu(UUR) from peripheral blood leukocytes (P<0.05). No severe adverse events were associated with taurine. Conclusions: The current study demonstrates that oral taurine supplementation can effectively reduce the recurrence of stroke-like episodes and increase taurine modification in mitochondrial tRNA Leu(UUR) in MELAS. Trial registration number: UMIN000011908.